In a time of torment - Stone, I. F. (Randome House, 1967)
A view of America in the Sixties is offered in this collection of journalistic writings. The pieces cover the Cuban missile crisis, the Kennedy assassination, the violent white reaction to civil rights legislation and the rise of black power, Vietnam and the student riots.